A naturalistic longitudinal analysis of post‐detoxification outcomes in opioid‐dependent patients. (20th September 2017) - Ivers, Jo‐Hanna; Zgaga, Lina; Sweeney, Brion; Keenan, Eamon; Darker, Catherine; Smyth, Bobby P.; Barry, Joe
Abstract: Introduction and Aims: To provide an assessment of outcomes in a cohort of opioid‐dependent patients post‐detoxification. Design and Methods: This study employed an observational longitudinal cohort design. Patients who completed detoxification in the three major Drug Dependency Units in Ireland during a 14‐month period were included in the study (n = 143). Patients opting for one of the three pathways post‐detoxification (inpatient aftercare, outpatient aftercare or no formal aftercare) were assessed in the final week of detoxification and followed up after 3, 6 and 9 months. The primary outcome was abstinence following detoxification. Results: A Cox (adjusted) model indicated participants who opted for outpatient aftercare treatment lapsed/relapsed at a rate of 52% higher than the inpatient aftercare group (hazard ratio = 1.52, 95% confidence interval 0.75–3.08, P = 0.24). Moreover, time to lapse/relapse was considerably shorter for the no formal aftercare group (hazard ratio = 7.68, 95% confidence interval 4.30–13.73, P = 5.75 × 10 −12 ). Abstinence rates for outpatient aftercare and inpatient aftercare are about equal after 9 months. Discussion and Conclusion: Patients who opt for aftercare post‐detoxification have significantly better outcomes at follow up when compared to no formal aftercare. In addition, patients' intention to attend aftercare affected their outcomes regardless of eventual treatment path.